Exploring the limitations of osmotically assisted reverse osmosis: membrane fouling and the limiting flux - Peters, Christian D. (2022)
Osmotically assisted reverse osmosis (OARO) has shown great potential for low-cost and energy-efficient brine management. However, its performance can be significantly limited by membrane fouling. Here, we performed for the first time a comprehensive study on OARO membrane fouling, explored the associated fouling mechanisms, and evaluated fouling reversibility via simple physical cleaning strategies. First, internal membrane fouling at the draw (permeate) side was shown to be insignificant. Flux behavior in short-term operation was correlated to both the evolution of fouling and the change of internal concentration polarization. In long-term operation, membrane fouling constrained the OARO water flux to a singular, common upper limit, in terms of limiting flux, which was demonstrated to be independent of operating pressures and membrane properties. Generally, once the limiting flux was exceeded, the OARO process performance could not be improved by higher-pressure operation or by utilizing more permeable and selective membranes. Instead, different cyclic cleaning strategies were shown to be more promising alternatives for improving performance. While both surface flushing and osmotic backwashing (OB) were found to be highly effective when using pure water, a full flux recovery could not be achieved when a nonpure solution was used during OB due to severe internal clogging during OB. All in all, the presented findings provided significant implications for OARO operation and fouling control.